Tomada de decisão na produção de cana de açúcar pelos fornecedores na região de Jaú-SP, sob condições de risco - Minarelli, Philipp Herbst [UNESP] (2016)
The inclusion of uncertainty in an analysis model presents information relevant to sugar cane suppliers to the region of Jaú(São Paulo) and gains importance in studies where they compared several investment projects, as it allows the use of another tool for making decision. The analysis of economic indicators for investment projects in the sector aims to identify the competitiveness of sugar cane production costs. Given the great uncertainty that pervades the sugarcane industry, as domestic policy, productivity, quality of raw material. The study aimed to determine, by calculating the net present value and internal rate of return, the viability of sugarcane production in region of Jaú of grower status under risk conditions, using Monte Carlo simulation. The assessed economic indicators fluctuated against four critical variables: (1) productivity of sugar cane at different ages; (2) quality of raw material (TRS - Total Recoverable Sugar); (3) price paid to the supplier; (4) interest rate. The probability of these critical variables distribution functions were estimated and included in the Net Present Value (NPV) and Internal Return Rate (IRR) equations and using the Monte Carlo simulation, the following set of indicators were estimated: the indicators sensitivity analysis in relation to the critical variables, variability NPV and the IRR values and finally risk mapping for investors to provide cane sugar based on the model in this work for the region of Jaú. These indicators allowed to draw economic scenarios associated with their probability of occurrence. The results show that the grower of sugar cane in the region of Jaú/SP is, for the adopted model, a high-risk activity and the price paid to the supplier, the interest rate (SELIC) and the quality of the raw material the largest offenders order to achieve satisfactory profitability levels, wherein the positive benefits were found to lower probability than 40%. The variable with the greatest effect on profitability was the selling price of the product, and also the important cost cutting, loading and transportation.